Do Religiosity and Ethnocentrism Influence Indian Consumers’ Unwillingness to Buy Halal-Made Products? The Role of Animosity Toward Halal Products - Tao, Meng; Lahuerta-Otero, Eva; Alam, Faizan; Aldehayyat, Jehad Saleh; Farooqi, Md. Rashid; Zhuoqun, Peng (Frontiers in Psychology, 2022)
The purpose of this research is to assess the relationship between Indian (Hindu) consumers’ animosity toward halal products and their unwillingness to buy halal products. Moreover, we seek to investigate boycott attitudes, religiosity, ethnocentrism, and patriotism as drivers of consumer animosity and reluctance to purchase halal products. Consumer animosity toward halal products has received some attention in marketing research, and we aim to further explore animosity regarding the halal label. We collect online survey responses from 512 Indian consumers and analyze the data using SmartPLS3 software. Findings show a positive impact of boycott attitude, religiosity, and ethnocentrism on Indian consumers’ level of animosity and thus their unwillingness to purchase halal products. Furthermore, consumer animosity acts as a mediator of the relationship between boycott attitude, religiosity, ethnocentrism, patriotism, and reluctance to buy halal products. Notably, the findings provide a menu of potential managerial actions to reduce or enhance consumer animosity.